COOKING UP A NATION: PERCEPTIONS OF ENGLISH COOKERY, 1830-1930 - Goldstein, Lauren (My University, 2015)
This dissertation explores the origin of the idea that English food is inherently “bad” and demonstrates that this perception developed in the mid-nineteenth century. While it is commonly assumed that the poor quality of English cookery developed after the Second World War, this dissertation demonstrates that English cookery was perceived poorly beginning in the nineteenth century. This dissertation brings together an analysis of Victorian values, gender, food adulteration, food technologies, and nostalgia to establish how the English criticized themselves and created the belief that English cookery is “bad.” By examining cookbooks and newspaper articles, this investigation illustrates how the English criticized their own cooking and developed a sense of anxiety about their perceived flawed cookery. In the nineteenth century, cookery was evaluated based on emerging Victorian moral values rather than taste. The emphasis on being economical, efficient, and clean meant that traditional English dishes such as roast beef and plum pudding were no longer celebrated, but instead, considered wasteful and monotonous. Increasing imports through advances in shipping, refrigeration, and canning decreased the production of English goods at home. The adaptation and absorption of new imported ingredients and dishes into English cookbooks created a cosmopolitan cookery by the twentieth century, but, at the same time, deepened confusion over what an English food identity was. By studying cookbooks, this dissertation uses an untapped resource to explore the perception of English cookery. Cookbooks, especially mass publications, helped further the belief that English cookery was wasteful and unclean, and prescribed countless remedies for readers. Cookbooks also offered another perspective for exploring gender and cookery, as middle class women found themselves multitasking as housewives, educators, and cooks. More than just a collection of recipes, cookbooks provide historians with windows to view ideas of food identity, community, and culture.
Keywords: British history, cookery, identity